Dietary buckwheat enhances sirtuin1 without calorie restriction. (July 2020) - Pande, Shubhra; Ranjan, Rajeev; Shuvaev, Anton N.; Malinovskaya, Natalia A.; Ryazanova, Maria; Salmina, Alla B.; Kolenchukova, Oksana A.; Kratasyuk, Valentina A.
Abstract: In the present investigation, the role of dietary intervention in male Wistar rats ( n  = 8, 3 groups) was studied to observe absolute sirtuin 1 (SIRT1) levels (expressed as ng mg −1 total protein) in serum, stomach, liver, and kidney. Dietary buckwheat at 30% (w/w) level of incorporation in the standard diet (Buckwheat Enriched Diet, BED) improved SIRT1 with values 0.933 ± 0.05, 210 ± 7, 63.26 ± 4, and 69.89 ± 3 in serum, stomach, liver, and kidney respectively when compared to the respective control values of 0.536 ± 0.03, 156 ± 23.3, 31.07 ± 2 and 47.11 ± 4. Moreover, BED though isocaloric to CR diet, led to weight gain (g) by 63.11 ± 3.8, ca. 10%, and 40% higher than control (56.27 ± 5.6) and CR (45.05 ± 4.1) diet groups. A marked rise in Feed Efficiency Ratio (FER) by ca. 37% while a 30% decrease in Feed Conversion Ratio (FCR) was observed for the BED group which supports unexpected weight gain in rats post-dietary intervention. The results justify the superior nutritional profile of buckwheat laden with essential nutrients, essential proteins, and bioactives. In contrast, Calorie Restriction (CR) resulted in a decline of the total protein content in circulation by 19%, while reduction of total protein in stomach, liver, and kidney was estimated to be 95%, 35.2%, and 27% respectively though SIRT1 values were comparatively the highest in all the samples studied. A 30-fold enhancement of SIRT1 in stomach post CR is presumed to counter enhanced stress in gastric tissues. Therefore, mild to moderate expression of SIRT1 may confer beneficial effects such as delayed aging and stress resistance but exceedingly high SIRT1 may evoke increased oxidative stress. Graphical abstract: Image 1 Highlights: Buckwheat enriched diet improves Sirtuin 1 in optimum without calorie restriction. A 30-fold rise of sirtuin 1 in stomach post calorie restriction indicates enhanced stress. Negative impact of calorie restriction include loss of total protein in organ of rats. Absolute values of Sirtuin 1 is determined in serum, stomach, liver, and kidneys.